Are the researcher and the reviewer focused on defending the journal’s credibility in the face of scientific demands? - Fontoura Filho, Carlos (Scientific Journal of the Foot & Ankle, 2018)
The last editorial highlighted the importance of the internationalization of this journal as well as the use of well-defined standards and agile and modern mechanisms for the rapid publication of scientific material. In this scenario, there is concern about building a good level of content. A revival of the scientific tradition and the modernization (but not replacement) of the method and forms of review, from standardizations brought about by experimentalism to the inclusion of digital technology, are called for. In an academic universe in which publication volume transcends optimistic expectations, new journals and scientific portals with global and instantaneous reach appear at every moment. Modernity is, according to Zygmunt Bauman1, liquid. Scientific production gallops. However, readers look for the best-supported content, recognizing that it is impossible to read every published article within their area of interest. With their good power of discernment, they choose more useful and higher-quality articles, leaving aside irrelevant ones. It is not wrong to state that an unread article is a lost article. Moses Naim2, in his book "The End of Power", notes that it is increasingly feasible for a competent bureaucratic institution to achieve its optimal conceptual level and gain space in an environment in which traditional and powerful institutions already exist in the same segment. The barriers that protect the power of larger institutions are increasingly fragile. The digital age and the internet (mobility), the growing number of alternatives for the same product (more) and increasing intellectual preparation (mentality) help to break down these barriers that preserve the power of traditional organizations. For the same reasons, a newly ascended entity can easily lose its prominence. This phenomenon is what this author calls the revolution of the three “m’s”: more, mobility and mentality. This journal navigates in this sea of contemporary events, within which economic liberalism, for example, insinuates itself, albeit late. The large volume of publications entails a predictable bias toward a great variety of content and, concurrently, an increase in the spectrum of methodological quality in both the higher and lower directions. This new reality calls on participants who are coherent and aware of their role in steering the "Scientific Journal" along the stormy sea route of a busy and demanding market. It may be difficult to apply ideas that appear to be obvious: researchers need to produce relevant material with good scientific quality and sound methodology, and reviewers must match researchers’ efforts by devoting the same scientific competence, ethics and dedication to the production that they receive. Therefore, it is important to ask how, within a national context, researchers and reviewers can be prepared, mobilized, updated and improved such that they conduct their work in "firm steps" with good methods and well-applied tools. See "Liquid Modernity" by Zygmunt Bauman, in which the author, a Polish sociologist and World War II refugee based in Great Britain, considers immediate modernity "light", "liquid", "fluid" and immensely more dynamic than "solid" modernity, which would have been dethroned. Moisés Naím is a Venezuelan writer and columnist who has been the editor-in-chief of Foreign Policy magazine since 1996. He has written on international politics and economics, economic development, multilateral organizations, US foreign policy and the unintended consequences of globalization. Carlos Fontoura Filho Review Board, Scientific Journal of the Foot & Ankle Doctor in Medicine, Medical School, University of São Paulo (USP) in Ribeirão Preto Adjunct Professor of Orthopedics and Traumatology, Medical School, Federal University of Triângulo Mineiro Reply to Professor Dear Prof. Dr. Carlos Fontoura Filho, First of all, thank you for your appreciation. I was motivated when I read your letter and I was sure that our work is being pursued with a focus on best practices. Significant efforts are being expended to achieve our goals. An interesting aspect to highlight is how editorial processes can suffer external influences, even in scientific environments, where the ethical conduct of authors, reviewers and editors must be above all else. Practicing medicine under the aegis of ethics requires of the physician a broad experience in this social, moral environment, and constant updating, far beyond the strictly technical requirements. We are much more demanded in the multiple aspects of human relations, if compared to other professions. We must keep careful attention on all those aspects that govern the principles of education and training of young people not only as orthopedic surgeons of the foot and ankle but also as citizens of the world. Jorge Mitsuo Mizusaki Editor-in-chief